Pegylated arginine deiminase depletes plasma arginine but maintains tissue arginine availability in young pigs - Mohammad, Mahmoud A. (Am J Physiol Endocrinol Metab, 2021)
Pegylated arginine deiminase (ADI-PEG20) results in the depletion of arginine with the production of isomolar amounts of citrulline. This citrulline has the potential to be utilized by the citrulline recycling pathway regenerating arginine and sustaining tissue arginine availability. The goal of this research was to test the hypothesis that ADI-PEG20 depletes circulating arginine in pigs but maintains tissue arginine concentration and function, and to characterize the kinetics of citrulline and arginine. Two multitracer approaches (bolus dose and primed-continuous infusion) were used to investigate the metabolism of arginine and citrulline in Control (n = 7) and ADI-PEG20 treated (n = 8) pigs during the postprandial period. In addition, blood pressure was monitored by telemetry, and multiple tissues were collected to determine arginine concentration. Plasma arginine was depleted immediately after ADI-PEG20 administration, with an increase in plasma citrulline concentration (P < 0.01). The depletion of arginine did not affect (P > 0.10) blood pressure, whole body protein synthesis, or urea production. Despite the lack of circulating arginine in ADI-PEG20-treated pigs, most tissues were able to maintain concentrations similar (P > 0.10) to those in Control animals. The kinetics of citrulline and arginine indicated the high citrulline turnover and regeneration of arginine through the citrulline recycling pathway. ADI-PEG20 administration resulted in an absolute and almost instantaneous depletion of circulating arginine, thus reducing global availability without affecting cardiovascular parameters and protein metabolism. The citrulline produced from the deimination of arginine was in turn utilized by the citrulline recycling pathway restoring local tissue arginine availability. NEW & NOTEWORTHY Pegylated arginine deiminase depletes circulating arginine, but the citrulline generated is utilized by multiple tissues to regenerate arginine and sustain local arginine availability. Preempting the arginine depletion that occurs as result of sepsis and trauma with arginine deiminase offers the possibility of maintaining tissue arginine availability despite negligible plasma arginine concentrations.